A survey of microbiological quality of fish sold in two local wet markets - Rahmat Ali, Gulam Rusul; Mohd Dahan, Mohamed Mahyuddin; Dollah, Mustafa (1991)
Eight marine fish species were obtained from two nearby wet markets (Sungei Besi and Kajang). The fish were analysed for total viable counts, coliforms, Vibrio parahaemolyticus and histamine-producingbacteria. Total viable count was determined using Plate Count Agar; coliforms using McConkey Broth; Vibrio parahaemolyticus by TCBS a garand histamine-producing bacteria were determined using Niven's media. The total counts on all fish from both markets ranged from 1rf to 1rf per gram offish, coliforms ranged from 1rJ to 1rf pergram, and all thefish examined were positive for both Vibrio parahaemolyticus and histamine-producing bacteria.